Child vaccination programme in family doctor practices in 1997–2015: a cross-sectional study in Białystok, Poland - Anna Owłasiuk; Dorota Emilia Bielska; Anna Gryko; Ludmiła Marcinowicz; Marek Czajkowski (Pediatria i Medycyna Rodzinna, 2018)
Introduction: Vaccination is the most effective method of infectious disease prevention. Contemporary technologies have created the possibility of producing vaccines against many diseases. Their use has been facilitated due to the development of combined vaccines aimed at multiple microorganisms. Vaccine regimens differ between countries depending on their epidemiological and population needs. Aim of the study: Assessment of vaccination programme implementation among young patients, including with the use of combined and recommended vaccines in family doctor practices in Białystok, Poland, in 1997–2015. Material and methods: The research material constituted medical records of children aged 0–19 years who were under the care of three family doctor practices in the city of Białystok, Poland. Vaccination cards of 2,804 children born in 1997–2015 have been analysed. Results: Under the official vaccination programme 98.43% of children have been immunised; 42.0% of them received combined pentavalent or hexavalent vaccines (financed by parents) in place of free-of-charge, state-reimbursed vaccines. Recommended vaccines were received by 45.7% of children and adolescents. Recommended vaccinations were rarely used in children aged over 10 years. Among non-mandatory vaccines the most commonly used ones included acellular pertussis component vaccine, which was used to immunise 1,178 (42.0%) children, Streptococcus pneumoniae vaccine (18.1%) and rotavirus vaccine (13.0%). Due to a lack of parental consent or contraindications (temporary or permanent) 81 (2.9%) children have not received a full set of vaccinations. Conclusions: 1) The vaccination rate among children receiving mandatory vaccines is high in family doctor practices. 2) Recommended vaccines are more frequently administered to children up to 3 years of age, less frequently to preschool children and even less frequently to schoolchildren. 3) There is a need for parent education on the available effective methods of protecting children against infectious diseases.